Regulation of muscle plasticity and trophism by fatty acids: A short review - Abreu,Phablo (2017)
Summary The skeletal muscle tissue has a remarkable ability to alter its plastic structural and functional properties after a harmful stimulus, regulating the expression of proteins in complex events such as muscle regeneration. In this context, considering that potential therapeutic agents have been widely studied, nutritional strategies have been investigated in order to improve the regenerative capacity of skeletal muscle. There is evidence of the modulatory action of fatty acids, such that oleic and linoleic acids, that are abundant in Western diets, on muscle function and trophism. Thus, fatty acids appear to be potential candidates to promote or impair the recovery of muscle mass and function during regeneration, since they modulate intracellular pathways that regulate myogenesis. This study is the first to describe and discuss the effect of fatty acids on muscle plasticity and trophism, with emphasis on skeletal muscle regeneration and in vitro differentiation of muscle cells.